VD_FINDINFO HC / 2011 / 470 vom 16. August 2011 - VD Tribunal cantonal (2011)
DIRECTIVEINJONCTION, DÉBITEUR, OBLIGATION D'ENTRETIEN, ENFANT | 291 CC, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 317 al. 1 CPC (CH), 317 al. 2 CPC (CH)